Pemberdayaan Masyarakat Desa dalam Pengembangan Ekonomi Digital kepada Industri Kecil dalam Menghadapi Covid-19 di Desa Mentaren II Pulang Pisau - Indah Tri Handayani; Bahrianoor Bahrianoor (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The village of Mentaren II is productive as the center of the snack processing industry. The majority of the people use agricultural land as a livelihood to make various snacks. The management of small industries in this village has been going on for a long time; business actors have their own materials and equipment in their processing practices. Pukades is one of the leading village programs in the direction of development in the village. With this superior village product, it is hoped that it can boost job opportunities in the countryside. So that systematically, it can increase purchasing power and reduce the level of poverty in the village. The sales prospect is quite developed, as evidenced by the many results of their complaining that they are traded in suburban stalls along the Kalimantan road, even directly with buyers. However, this industry's development has faced obstacles since the Covid-19 epidemic, which requires the public not to gather together. This has an impact, especially on business actors who have been relying on conventional marketing systems. At this stage, the community service team visits the village office and meets the village head and village officials, discussing village institutions' activeness, both BUMDes, and Posyantek, in the village. The service team immediately went into the field by visiting several houses that had businesses and conducting brief interviews with the procession of managing activities and various obstacles.